FTAA 2005 : an agenda for progress : a discussion paper - Katz, Julius L. (Council of the Americas WashingtonUS, 1996)
Outlines a series of commitments that governments should adopt as a means of significantly improving the near and medium-term climate for business activity in the region, for in so doing they would greatly ease the ultimate negotiations of the FTAA and re-energize the spirit of Miami.